2014
DOI: 10.5507/bp.2012.105
|View full text |Cite
|
Sign up to set email alerts
|

Effect of spironolactone in patients with resistant arterial hypertension in relation to age and sex: Insights from the aspirant trial

Abstract: Background. There are currently limited data on whether the effect of spironolactone in patients with resistant arterial hypertension depends on age and sex. Methods. Patients with an office systolic blood pressure (BP) >140 mmHg or diastolic BP >90 mmHg, despite treatment with at least 3 antihypertensive drugs including a diuretic, were randomly assigned to receive spironolactone or a placebo for 8 weeks in a double-blind, placebo-controlled, multicentre trial (ASPIRANT). Results. Analyses were done on 55 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Keeping this in mind, we decided not to insist on complete exclusion of secondary hypertension before enrollment into the trial, as these measures would not be possible in certain developing countries. In our previous analyses, we showed that spironolactone treatment is effective to a similar extent both in patients with and without a secondary cause of hypertension, 36 and its antihypertensive efficacy seemed to be higher in elderly patients age >62 years 37 . The current analysis confirmed that the presence of more than one-fourth of patients with subsequently found secondary forms of hypertension did not change the overall trial results.…”
Section: Discussionmentioning
confidence: 89%
“…Keeping this in mind, we decided not to insist on complete exclusion of secondary hypertension before enrollment into the trial, as these measures would not be possible in certain developing countries. In our previous analyses, we showed that spironolactone treatment is effective to a similar extent both in patients with and without a secondary cause of hypertension, 36 and its antihypertensive efficacy seemed to be higher in elderly patients age >62 years 37 . The current analysis confirmed that the presence of more than one-fourth of patients with subsequently found secondary forms of hypertension did not change the overall trial results.…”
Section: Discussionmentioning
confidence: 89%